Boris Groys and the total art of Stalinism. (June 2019) - He, Yanli
This paper's core concern is Boris Groys' theory of the total art of Stalinism, which is devoted to rewriting Soviet art history and reinterpreting Socialist Realism from the perspective of the equal rights between political and artistic Art Power. The aim of this article is to decode Groys and the total art of Stalinism, based on answering the following three questions: 1) why did Groys want to rewrite Soviet art history? 2) How did Groys re-narrate Soviet art history? 3) What are the pros and cons of his reordering of the total art of Stalinism? Groys offers an effective paradigm that could rethink two theoretical genres: a) other Socialist Realisms inside or outside the Soviet bloc, during or after the Soviet era; b) the aesthetical rights of political artworks before, during and after the Cold War, and the historical debates about art, especially about art for art's sake, or art for political propaganda. However, Groys' total art of Stalinism and its core theory of the Socialist Realism frame hides some dangers of aestheticizing Stalin and Stalinism.